Highly-sensitive H2S sensors based on flame-made V-substituted SnO2sensing films - J. Sukunta (2018)
© 2016 Elsevier B.V. In the present work, 0–2 wt% vanadium (V)-doped SnO 2 nanoparticles synthesized by flame spray pyrolysis were systematically studied for H 2 S detection. The sensing films (∼15–20 μm in thickness) were homogeneously prepared by spin coating technique on Au/Al 2 O 3 substrates. Structural characterizations by electron microscopy and X-ray analysis confirmed the formation of agglomerated SnO 2 nanoparticles (5–20 nm) with highly crystalline tetragonal-cassiterite SnO 2 structure and V substitutional doping with mainly V 5+ oxidation state. The gas-sensing studies revealed that the H 2 S response of flame-made SnO 2 nanoparticles was significantly enhanced by V doping at a very low concentration of 0.1 wt% but the response steadily degraded as the V-doping level increases further up to 2 wt%. In particular, the 0.1 wt% V-doped SnO 2 sensor exhibited a very high response of 2274 with a short response time of 2.0 s to 10 ppm of H 2 S at 350 °C. Moreover, the V-doped SnO 2 sensor displayed high H 2 S selectivity against NO, NO 2 , SO 2 , H 2 , C 2 H 5 OH and CH 4 . Hence, the flame-made V-doped SnO 2 sensor is a promising candidate for highly sensitive and selective of H 2 S monitoring and may be useful for general industrial applications.